HER+ Initiative dissects women’s empowerment and climate resilience in West Bengal using Pro-WEAI - International Rice Research Institute (International Rice Research Institute, 2024)
Under the CGIAR Gender Impact Platform’s Methods Module, the CGIAR Initiative on Gender Equality (HER+) was granted USD100,000 to apply and scale the Women’s Empowerment in Agriculture Index (WEAI) and similar tools and metrics to their climate change research.